Hydrothermal synthesis of caterpillar-like one-dimensional NiCO3 nanosheet arrays and primary lithium battery application. Issue 17 (19th April 2022) - Cheng, Cuixia; Chen, Fang; Cheng, Yinfang; Lai, Guosong
Abstract : Transition metal carbonates have shown great potential as anode materials for next-generation lithium-ion batteries (LIBs), due to their super-high capacity. Abstract : Transition metal carbonates have shown great potential as anode materials for next-generation lithium-ion batteries (LIBs), due to their super-high capacity. However, pure-phase NiCO3 with high electrochemical activity has not been reported to date. Herein, highly uniform caterpillar-like one-dimensional (1D) NiCO3 nanosheet arrays have been successfully synthesized using a facile hydrothermal route and have been evaluated as an anode material for LIBs. Profiting from the unique 1D hierarchical structure and spaces between the neighboring nanosheets, the as-prepared NiCO3 requires lower activation energy and delivers quick lithium-ion diffusion kinetics. These attributes result in a high capacity of 893 mA h g −1 after 150 cycles and excellent rate performance, superior to those of most reported transition metal carbonates. Cyclic voltammetry, ex situ X-ray diffraction and X-ray photoelectron spectroscopy reveal the lithium storage mechanism.